2014
DOI: 10.1016/j.euroecorev.2013.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Labor diversity and firm productivity

Abstract: Using a matched employer-employee data-set, we analyze how workforce diversity associates with the productivity of rms in Denmark, following two main econometric routes. In the rst one, we estimate a standard Cobb-Douglas function, calculate the implied total factor productivity and relate the latter to diversity statistics in a second stage. This reduced-form approach allows us to identify which types of labor heterogeneity appear to descriptively matter. In the second approach, we move toward a richer produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
139
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(155 citation statements)
references
References 58 publications
11
139
1
4
Order By: Relevance
“…However, the output elasticity with respect to foreign knowledge of immigrant managers is lower than that of high skilled immigrants without executive functions and becomes insignificant in the fully specified model, controlling for the full range of occupational positions of the employed immigrants. Additionally, we confirm existing findings that workforce ethnic diversity is associated with a negative output elasticity (e.g., Parrotta et al, 2014a). Despite our negative impact of workforce ethnic diversity on firms' gross production, perhaps, through increased communication costs, our findings point to the economic importance of a diverse labour force for the firm's capability to access international knowledge.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…However, the output elasticity with respect to foreign knowledge of immigrant managers is lower than that of high skilled immigrants without executive functions and becomes insignificant in the fully specified model, controlling for the full range of occupational positions of the employed immigrants. Additionally, we confirm existing findings that workforce ethnic diversity is associated with a negative output elasticity (e.g., Parrotta et al, 2014a). Despite our negative impact of workforce ethnic diversity on firms' gross production, perhaps, through increased communication costs, our findings point to the economic importance of a diverse labour force for the firm's capability to access international knowledge.…”
Section: Introductionsupporting
confidence: 79%
“…The estimates in column (1) Another notable result of the analysis is the negative sign associated with the ethnic diversity measure which is in line with previous studies. Prior research has shown the negative effect of diversity on firms' economic performance (Parrotta et al, 2014a). The argument is that eth-nic diversity comes along with costs and benefits for firms' productivity.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies at the establishment or firm level mostly focus on other outcomes such as patenting activities (see Ozgen et al 2011, Audretsch et al 2010, Chellaraj et al 2008, thereby contributing to the related discussion how diversity affects innovation (also see Niebuhr 2010 andNathan 2011). The study by Parrotta et al (2010) is also related to ours, as they estimate the productivity effects of workforce diversity among Danish firms. However, they do not focus on the important question whether spillovers from diversity arise mainly at the micro or at the aggregate level.…”
mentioning
confidence: 99%
“…(ix) over dependence on development assistance (Asongu, 2014c;Oben-Odoom, 2013;Moyo, 2009) or Western-oriented policies (Fofack, 2014); (x) Washington consensus and lost decades (Lin, 2015), partially because of the false economics of preconditions (Monga, 2014); (xi) the evolving interest in the impacts of diversity on economic prosperity (Hjort, 2014;Parrotta et al, 2014 ) and a novel strand of literature on epigenetics, genetics and economics (Fedderke et al, 2014); (xii) corruption in international trade (Musila & Sigué, 2010) and policies on rational asymmetric development (Asongu, 2015a); (xiii) low-degree of regional integration (Kayizzi-Mugerwa, et al, 2014); (xiv) the failure to integrate qualitative measurements of progress into the development paradigms of Africa (Obeng-Odoom, 2013) and (xv) the absence of conducive local conditions, presence of fragile institutions and the incapacity to effectively negotiate foreign aid conditions (Kayizzi-Mugerwa, 2001). …”
Section: Figure 1: Comparative Regional Poverty Levelsmentioning
confidence: 99%